Cytokinin‐induced promotion of root meristem size in the fern Azolla supports a shoot‐like origin of euphyllophyte roots. Issue 2 (11th September 2015) - de Vries, Jan; Fischer, Angela Melanie; Roettger, Mayo; Rommel, Sophie; Schluepmann, Henriette; Bräutigam, Andrea; Carlsbecker, Annelie; Gould, Sven Bernhard
Summary: The phytohormones cytokinin and auxin orchestrate the root meristem development in angiosperms by determining embryonic bipolarity. Ferns, having the most basal euphyllophyte root, form neither bipolar embryos nor permanent embryonic primary roots but rather an adventitious root system. This raises the questions of how auxin and cytokinin govern fern root system architecture and whether this can tell us something about the origin of that root. Using Azolla filiculoides, we characterized the influence of IAA and zeatin on adventitious fern root meristems and vasculature by Nomarski microscopy. Simultaneously, RNAseq analyses, yielding 36 091 contigs, were used to uncover how the phytohormones affect root tip gene expression. We show that auxin restricts Azolla root meristem development, while cytokinin promotes it; it is the opposite effect of what is observed in Arabidopsis . Global gene expression profiling uncovered 145 genes significantly regulated by cytokinin or auxin, including cell wall modulators, cell division regulators and lateral root formation coordinators. Our data illuminate both evolution and development of fern roots. Promotion of meristem size through cytokinin supports the idea that root meristems of euphyllophytes evolved from shoot meristems. The foundation of these roots was laid in a postembryonically branching shoot system.